factorise the following trinomials b^2+2b+1
Answers
Answered by
2
Answer:
(b+1)^2
Step-by-step explanation:
→b^2+2b+1
=b^2+2(1)(b)+1^2→equation (1)
a=b,b=1
- the equation (1) is in the form of a^2+b^2+2ab=(a+b)^2,where a=b and b=1.
so,b^2+2b+1 =(b+1)^2
hence,(b+1)^2 is the solution.
I HOPE IT HELPS YOU
Answered by
0
Answer:
(b+1)²
step-by-step answer:
b² + 2b + 1
Rewrite 1 as 1²
b² + 26 + 1²
Check the middle term by multiplying 2ab and compare this result with the middle term in the original expression.
2ab = 2. b. 1
Simplify.
2ab = 26 =
Factor using the perfect square trinomial rule
a² + 2ab + b = (a + b)², where a = b and b = 1.
(b+1)²
Similar questions